Investigation of Genetic Structures of Coloured Horses by mtDNA D-loop Sequence Analysis in Turkey - Koseman, Abdurrahman; Ozsensoy, Yusuf; Erdogan, Metin; Yarali, Cevdet; Toprak, Burhan; Zengin, Kemal; seker, Ibrahim (Kafkas Univ, Veteriner Fakultesi Dergisi, 2019)
The aim of this study was to determine the genetic structure of Coloured horses in Turkey by analysis of the D-loop sequence of mitochondrial DNA (mtDNA). A total of 28 Coloured horses were examined. DNA was extracted from blood samples using DNA isolation kit; 519 bp long mtDNA D-loop region was amplified by PCR and sequenced by capillary electrophoresis system. Population parameters and phylogenetic trees were drawn by using MEGA4 software package. It was also compared with the DNA sequences of horse populations from different countries. In this study, 42 different polymorphism regions and 10 different haplogroups were detected. Additionaly, Tajima D value was found to be -0.31 and population expansion was determined. It was determined that the base differences among the horses ranged between 0.000 and 0.032. It was detected that the horses formed different clusters from each other and they were intertwined with the populations of different countries. Moreover, it was also observed that some horses formed their own populations at different points from the other countries' horses. As a result, it was observed that the genetic structures of horses which used in population were different from each other and they originated from different mothers. According to the results obtained, it is considered that Coloured horses can be a native horse breed of Turkey.
Türkiye’deki alaca atların mtdna d-loop dizi analizi ile genetik yapılarının araştırılması
International Congress on Agriculture and Animal Sciences (ICAGAS) -- NOV 07-09, 2018 -- Antalya, TURKEY
Keywords: Coloured horse; D-loop region; Haplogroup; Mitochondrial DNA